High Antigen Dose Is Detrimental to Post-Exposure Vaccine Protection against Tuberculosis - Billeskov, Rolf; Lindenstrøm, Thomas; Woodworth, Joshua; Vilaplana, Cristina; Cardona, Pere-Joan; Cassidy, Joseph P.; Mortensen, Rasmus; Agger, Else Marie; Andersen, Peter (Frontiers in Immunology, 2018)
Mycobacterium tuberculosis (Mtb), the etiologic agent of tuberculosis (TB), causes 1.8M deaths annually. The current vaccine, BCG, has failed to eradicate TB leaving 25% of the world’s population with latent Mtb infection (LTBI), and 5–10% of these people will reactivate and develop active TB. An efficient therapeutic vaccine targeting LTBI could have an enormous impact on global TB incidence, and could be an important aid in fighting multidrug resistance, which is increasing globally. Here we show in a mouse model using the H56 (Ag85B-ESAT-6-Rv2660) TB vaccine candidate that post-exposure, but not preventive, vaccine protection requires low vaccine antigen doses for optimal protection. Loss of protection from high dose post-exposure vaccination was not associated with a loss of overall vaccine response magnitude, but rather with greater differentiation and lower functional avidity of vaccine-specific CD4 T cells. High vaccine antigen dose also led to a decreased ability of vaccine-specific CD4 T cells to home into the Mtb-infected lung parenchyma, a recently discovered important feature of T cell protection in mice. These results underscore the importance of T cell quality rather than magnitude in TB-vaccine protection, and the significant role that antigen dosing plays in vaccine-mediated protection.